(untitled) (Global Journal of Management and Business Research, 2015)
This paper proposes using "exercises" (articles to spur Socratic dialogue), a pedagogical innovation to foster learning of critical concepts in marketing. Exercises enable students relatively unfamiliar with business and strategic decision making to learn marketing theory by applying concepts to better understand and solve current problems confronting an actual company. By allowing students to apply concepts in specific, feature-rich, real contexts, exercises stimulate critical thinking ability in the best traditions of the Socratic method. Exercises inspire understanding, analysis, and problem solving through reading, reflection, discussion, and application of marketing concepts. Learning from peers by sharing information and applying marketing concepts to generate insights about compelling problems helps enhance student retention of critical ideas.